Investigation the effect of different sizes of hybrid maize (Zea mays L.) seed at different sowing dates on the emergence performance of seedling in field - Enayat Rezvani Khorshidi; Farshid Hasani; Mohammad Reza SHiri; Mehran Sharafizadeh; Aziz Moradi; Mohammad Rahmani; Aidin Hamidi; Mostafa Arabi (علوم و فناوری بذر ایران)
In order to study the effect of seed size of hybrid maize (KSC704) at different sowing times on the indices related to percentage, rate, vigor and uniformity of seed emergence in the field, an experiment was conducted in two years 2012 and 2013 as a factorial design in Karaj. The female rows (B73 inbred line) were pollinated by male rows (Mo17 inbred line) in each plot. After different seed were determined, they cultivated in the field in the next year. Medium seeds in the first year and flat seeds in the second year had significantly the highest field emergence percentages nad round seeds had the lowest in both years. Flat seeds produced seedlings with the highest dry weight in both years. But in the aspect of emergence uniformity of seedling, medium seeds had a higher uniformity than the others. Despite the superiority of flat seeds in some indices, its superiority was not a definite issue, and in some of the important emergence indices, medium and even the round size had better field performance, depending on the environmental conditions of growth and development of the seeds on the ears of mother plant and at sowing time, and the compression of the seeds in different points of the ear, as well as desired purpose of cultivation. If vigorous seedlings are needed, the flat seeds, but if a higher emergence rate and uniformity is desired, the medium seeds and even round seeds can be better suited